Generation of quantum steering and interferometric power in the dynamical Casimir effect - Sabín, Carlos; Adesso, Gerardo (American Physical Society, 2015)
We analyze the role of the dynamical Casimir effect as a resource for quantum technologies, such as quantum cryptography and quantum metrology. In particular, we consider the generation of Einstein-Podolsky-Rosen steering and Gaussian interferometric power, two useful forms of asymmetric quantum correlations, in superconducting waveguides modulated by superconducting quantum interferometric devices. We show that while a certain value of squeezing is required to overcome thermal noise and give rise to steering, any nonzero squeezing produces interferometric power which in fact increases with thermal noise.